2003
DOI: 10.1021/jp034904t
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Driven Shock Wave-Induced Triboluminescence of an Organic Crystal:  Toward a Semiquantitative Study

Abstract: A novel technique for studying triboluminescence (TL) of organic crystals is proposed. N-Isopropylcarbazole (NIPCz) crystals were fixed onto a glass plate, whose reverse side was coated with a black pigment that was used as a shock-generating layer. A single fundamental pulse from a Nd 3+ :YAG laser (1064 nm, fwhm ∼ 10 ns) was irradiated onto the shock-generating layer to generate a shock wave, and this resulted in both crystal fracture and TL from the NIPCz crystals. The TL spectrum was almost the same as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…Emission can be found from O ±,0 , N ±,0 , N 2 ±,0 , O 2 ±,0 , and C 2 ±,0 , along with that from the molecules comprising the crystals and fragment radicals. The light is called triboluminescence [11][12][13][14][15][16][17][18][19][20] and even laser induced shock waves external to the crystals can generate excited electronic states. 18,[21][22][23][24][25] Note that the ionization energy of N 2 itself is over 15.5 eV and this only generates N 2 + (X)!…”
Section: Introductionmentioning
confidence: 99%
“…Emission can be found from O ±,0 , N ±,0 , N 2 ±,0 , O 2 ±,0 , and C 2 ±,0 , along with that from the molecules comprising the crystals and fragment radicals. The light is called triboluminescence [11][12][13][14][15][16][17][18][19][20] and even laser induced shock waves external to the crystals can generate excited electronic states. 18,[21][22][23][24][25] Note that the ionization energy of N 2 itself is over 15.5 eV and this only generates N 2 + (X)!…”
Section: Introductionmentioning
confidence: 99%
“…The actual volume of adiabatically-compressed gas is probably larger than the shock-compressed liquid volume at the same shock pressure. We adopted this volume to calculate the gas temperature using formula (2). For example, for a shock pressure of 10.0 GPa, the volume of nitrogen gas is calculated to be 0.21 cm 3 /g from formula (1), which is $6 times smaller than the liquid nitrogen density (1.23 cm 3 /g).…”
Section: Residual Gas Temperature Under Adiabatic Compressionmentioning
confidence: 99%
“…In most cases, such light emission is attributed to thermal radiation because shock compression can easily heat the matter up to thousands of degrees, which gives off intense emission of light over the visible region [1]. In other cases, it is reported that triboluminescence (or mechanoluminescence) has been observed from shock-compressed luminescent materials in laser shock experiments [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the size also plays an important role in the triboluminescence and the spatial resolution of damage events. [21,22] Crystals achieved by recrystallization from ethanol are needles with lengths around 80 mm [ Figure 5(A)]. They can grow into giant single crystals [500 mm length, Figure 5 Figure 5(D), the triboluminescence of NHEt 3 Eu(dbm) 4 needles, as shown in Figure 5(A), was recorded using a commercially available digital camera.…”
Section: Triboluminescent Materialsmentioning
confidence: 99%